2005
DOI: 10.1007/s11167-005-0407-8
|View full text |Cite
|
Sign up to set email alerts
|

A New Agent for Modification of the Teflon Surface

Abstract: The possibility of preparing modification solutions from sodium naphthalenide wastes and their effect on Teflon adhesion were studied.Organometallic complexes of alkali metals (Li, Na, K) and aromatic hydrocarbons (diphenyl, naphthalene, anthracene, etc.) are widely used to enhance adhesion of inert polymers, including Teflon [1,2]. Wastes remaining after modifying the Teflon surface with Na-naphthalene complex comprise more than 70% of the initial active solution. The spent inactive solution containing variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…They reported that peroxy‐radicals formed when the powders were exposed to O 2 in the air during the surface modification process. They also reported these peroxy‐radicals were converted to hydroxyl and other functional groups by the process of washing with H 2 O 42 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…They reported that peroxy‐radicals formed when the powders were exposed to O 2 in the air during the surface modification process. They also reported these peroxy‐radicals were converted to hydroxyl and other functional groups by the process of washing with H 2 O 42 …”
Section: Resultsmentioning
confidence: 99%
“…The reaction mechanism of surface modification of poly (tetrafluoroethylene) (PTFE) powders with Na-naphthalenide system. 34,42,46 properties and IZOD impact resistance. As shown in Figure 4, the addition of the surface-modified PTFE powders into the epoxy system increased both the ultimate tensile and flexural strength values by up to 10 wt%.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations